The Influence of CITO Procurement on Pharmaceutical Supply Chains: Efficiency, Challenges, and Outcomes (American Journal of Medical Science and Innovation, 2025)
This paper investigates the role of CITO (Critical Item Time Order) procurement in optimizing pharmaceutical supply chains, particularly in contexts requiring rapid responses to urgent supply needs. CITO procurement is analyzed for its effectiveness in enhancing operational efficiency, cost management, and patient outcomes within healthcare settings. Through a comprehensive review of existing literature and case studies, the paper identifies both the strengths and challenges associated with CITO implementation. Key findings suggest that while CITO can significantly reduce lead times and stockouts, organizations must also address potential risks related to supplier quality and regulatory compliance. The study proposes strategies for optimizing CITO procurement processes, emphasizing the importance of technology and strong supplier relationships in ensuring reliable and timely access to critical medications. Ultimately, this research highlights CITO’s potential as a vital strategy in the evolving landscape of pharmaceutical supply chains, underscoring its relevance for improving healthcare delivery and patient care.